2019
DOI: 10.3390/en12132461
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Energy Simulation Integrated Process by Automated Extraction Module of the BIM Geometry Module

Abstract: Despite the international trend of actively utilizing BIM in the field of energy simulation, it is difficult to actively utilize BIM in domestic certification-related practice. As a result, the work process is not integrated and the work efficiency is reduced, such as the occurrence of redundant tasks. In this paper, the integrated process based on the BIM geometry information automated extraction module was presented and its effectiveness was reviewed and verified through self-developed automation module and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…With this software, the energy model was also obtained, with which the energy simulation and analysis were subsequently performed with the plugin for REVIT, INSIGHT 360 [58]. This software performs energy simulation in the cloud, using industry-leading, trusted and widely established DOE 2.2 and EnergyPlus [59] simulation engines, DOE 2.2 [60] being the calculation engine of the Calener Unified Tool, a general option [61], to perform energy certifications for buildings in Spain. Once the energy simulation was carried out, the INSIGHT 360 platform visualized and interacted with the results obtained, through diagrams and performance diagrams directly in a virtual model, which allowed studying both the current state of the building, as well as possible energy improvements on the building [62,63].…”
Section: Methodsmentioning
confidence: 99%
“…With this software, the energy model was also obtained, with which the energy simulation and analysis were subsequently performed with the plugin for REVIT, INSIGHT 360 [58]. This software performs energy simulation in the cloud, using industry-leading, trusted and widely established DOE 2.2 and EnergyPlus [59] simulation engines, DOE 2.2 [60] being the calculation engine of the Calener Unified Tool, a general option [61], to perform energy certifications for buildings in Spain. Once the energy simulation was carried out, the INSIGHT 360 platform visualized and interacted with the results obtained, through diagrams and performance diagrams directly in a virtual model, which allowed studying both the current state of the building, as well as possible energy improvements on the building [62,63].…”
Section: Methodsmentioning
confidence: 99%
“…To do so, professionals in these phases must be encouraged to explore many variations concerning building orientation, relative compactness, window-to-wall ratio and positioning of windows, opaque elements construction (light, medium or heavy), preliminary U-values of opaque elements and windows, shadings, and g-value of windows. A professional who is controlling the NZEB project deployment should encourage the professionals in project delivery to use BIM in order to minimize information loss and errors as well as reducing the redundant tasks when observing designing/modeling the elements of building that impact the energy performance [28]. The other important reason for encouraging the BIM use is the possibility of using preliminary (black-box) building energy simulation tools that are implemented in BIM-authoring software (e.g., Archicad, Allplan, Revit).…”
Section: The Nearly Zero-energy Building Gateway Project Control Methodsmentioning
confidence: 99%
“…The other approach is to extract data that is useful from BIM model which is than used for energy calculation that is based on standard which certain country adopted. Following this approach Choi et al [28] made a module in Python that extracts data from the IFC and they use this data for a calculation based on standard ISO 13790:2008. They declare this way more error-free when comparing it with manual input due to human error.…”
Section: Building Information Model As An Input For Energy Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, various studies have been carried out to overcome the existing barriers (Nemati et al, 2020;Kaneta et al, 2017). Also, a number of researchers are currently investigating the way of promoting BIM for real applications (Migilinskas et al, 2013;Kaneta et al, 2017), especially for energy consumption simulation purposes (Choi et al, 2019;Kamel and Memari, 2019;Pruvost and Scherer, 2017). The results of such studies have indicated that BIM can be efficiently used to reduce energy consumption and construction costs and to decrease the time of constructing a building.…”
Section: Journal Of Settlements and Spatial Planningmentioning
confidence: 99%